2011
DOI: 10.1016/j.psychres.2010.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the Yale–Brown Obsessive–Compulsive Scale (Y-BOCS) in a large sample of patients with schizophrenia or related disorders and comorbid obsessive–compulsive symptoms

Abstract: a b s t r a c t a r t i c l e i n f oIn the past decade there has been an increasing interest in the levels of obsessive-compulsive symptoms (OCS) found in patients with schizophrenia or related disorders. The widely acknowledged gold standard measure of the severity of OCS is the content-free version of the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS) (Goodman et al., 1989a,b). However, factor analytic research in patients with obsessive-compulsive disorder (OCD) provided varied results. So far no study has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 28 publications
4
31
1
Order By: Relevance
“…This is in agreement with a number of factor analytic studies indicating that obsessions and compulsions are only weakly correlated and that the Y-BOCS is best represented by two (obsessions versus compulsions; Boyette, Swets, Meijer, Wouters, & Authors, 2010;McKay, Danyko, Neziroglu, & Yaryura-Tobias, 1995) or three (obsessions, compulsions and resistance; Kim, Dysken, Pheley, & Hoover, 1994;Moritz et al, 2002) rather independent factors. However, we need to acknowledge that there are some exceptions, with studies reporting somewhat higher correlations between obsessions and compulsions (e.g., Gönner & Kupfer, in preparation;McKay et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with a number of factor analytic studies indicating that obsessions and compulsions are only weakly correlated and that the Y-BOCS is best represented by two (obsessions versus compulsions; Boyette, Swets, Meijer, Wouters, & Authors, 2010;McKay, Danyko, Neziroglu, & Yaryura-Tobias, 1995) or three (obsessions, compulsions and resistance; Kim, Dysken, Pheley, & Hoover, 1994;Moritz et al, 2002) rather independent factors. However, we need to acknowledge that there are some exceptions, with studies reporting somewhat higher correlations between obsessions and compulsions (e.g., Gönner & Kupfer, in preparation;McKay et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…This concept can be investigated in OCD by focussing on the resistance and control dimensions of the Yale-Brown Obsessive Compulsive Scale (Y-BOCS). Curiously, previous studies have suggested that resistance to symptoms, together with control over symptoms (Deacon and Abramowitz, 2005), decreases the internal consistency of the Y-BOCS (Woody et al, 1995) and loads on a third factor, independently from obsessive and compulsive constructs (Boyette et al, 2011;Kim et al, 1994). Importantly, Deacon and Abramowitz (2005) demonstrated a clear double dissociation between two factors in the Y-BOCS e 'Severity' and 'Resistance/Control'.…”
Section: Introductionmentioning
confidence: 94%
“…This instrument allows the rating of compulsions and obsessions separately on a five-point Likert-scale (0-4) yielding subtotal scores ranging from 0 to 20. The YBOCS is able to reliably assess the severity of OCS in schizophrenia (de Haan et al, 2006;Boyette et al, 2011).…”
Section: Clinical Assessmentsmentioning
confidence: 99%